2018
DOI: 10.20944/preprints201808.0356.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Beta Kumaraswamy Burr Type X Distribution and Its Properties

Abstract: We proposed a so-called Beta Kumaraswamy Burr Type X distribution which gives the extension of the Kumaraswamy-G class of family distribution. Some properties of this proposed model were provided, like: the expansion of densities and quantile function. We considered the Bayes and maximum likelihood methods to estimate the parameters and also simulate the model parameters to validate the methods based on different set of true values. Some real data sets were employed to show the usefulness and flexibility of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Generalized inverted K-G Physics data [72] Topp-Leone generalized inverted K model Physics data [73] K log-logistic Weibull model Failure times data [74] Exponentiated inverse K model Economic data [75] Beta K Burr Type X model Physics and medical data [76] Marshall-Olkin extended inverted K model Physics, failure and medical data [77] K generalized Kappa model Geological data [78] Cubic rank transmuted K model Food and industrial data [79] K Marshall-Olkin log-logistic model Physics data [67] Odd generalized exponential K model Geological and environmental data [80] K exponentiated U-quadratic model Medical data [81] K odd Burr-G Physics and engineering data [82] Exponentiated generalized K model Environmental, agriculture and engineering data [83] Size-biased K model Engineering data [84] K generalized power Weibull model Engineering data [85] Exponentiated K-Dagum model Income and lifetime data [61]…”
Section: Model Modeling Authorsmentioning
confidence: 99%
“…Generalized inverted K-G Physics data [72] Topp-Leone generalized inverted K model Physics data [73] K log-logistic Weibull model Failure times data [74] Exponentiated inverse K model Economic data [75] Beta K Burr Type X model Physics and medical data [76] Marshall-Olkin extended inverted K model Physics, failure and medical data [77] K generalized Kappa model Geological data [78] Cubic rank transmuted K model Food and industrial data [79] K Marshall-Olkin log-logistic model Physics data [67] Odd generalized exponential K model Geological and environmental data [80] K exponentiated U-quadratic model Medical data [81] K odd Burr-G Physics and engineering data [82] Exponentiated generalized K model Environmental, agriculture and engineering data [83] Size-biased K model Engineering data [84] K generalized power Weibull model Engineering data [85] Exponentiated K-Dagum model Income and lifetime data [61]…”
Section: Model Modeling Authorsmentioning
confidence: 99%
“…Although, this model received well attention over the years but one of its shortcomings comes when the covariates were modelled using the proportion p which does not involve a proportional hazard (PH) model, as it is the property of survival model which corresponds to the models' involving covariates. On the other hand, Martinez, Achcar, Jacome and Santos (2013), makes some observations in equation (1), as it provides an improper posterior result which includes the non-informative prior (uniform). It is actually the main reason for its drawback in the recent years which makes its tedious to apply the Bayesian technique with non-informative priors which is very common nowadays.…”
Section: Cure Rate Modelsmentioning
confidence: 99%
“…We observed that the function cannot be expressed in a closed form reference to the limitation propose by . The baseline probability density function of the Beta Kumaraswamy Burr X distribution with six parameters by Madaki et al (2018), is written as follows:…”
Section: Beta Kumaraswamy Burr X Model Formulationmentioning
confidence: 99%
“…Moreover, two methods of estimation were discussed. Reference [15] continued some studies on the beta generated Kumaraswamy-G family by proposing the beta generated Kumaraswamy Burr type X distribution. Some properties of the distribution were provided; the maximum likelihood estimation was also obtained, and the model was applied to a real data set.…”
Section: Introductionmentioning
confidence: 99%